Strategi Inovasi Bisnis Sebagai Upaya Peningkatan Keunggulan Kompetitif Dan Pertumbuhan Bisnis UMKM Industri Kreatif Di Era Digital - Rahayu Mardikaningsih; Didit Darmawan (STIKes Ibnu Sina Ajibarang, 2023)
This research explores business innovation strategies aimed at improving competitiveness and supporting the growth of creative industry Micro, Small and Medium Enterprises (MSMEs) in the digital era. A qualitative approach, used in this study, focused on knowledge of the challenges faced by creative industry MSMEs, the role of digital technology, and the innovative strategies they implement. The findings of this study underscore the key role of e-commerce, data-driven decision-making, collaboration, and enhanced customer experience on the competitiveness and growth of creative industry MSMEs. In addition, the findings also contribute that the implementation of business innovation strategies can give creative industry MSMEs a competitive advantage through unique products and services and innovative designs. MSMEs can produce a variety of new products and services by utilizing digital technology. This can increase market appeal and enable businesses to adapt to changing consumer trends